Exploring Changes in the Host Gut Microbiota During a Controlled Human Infection Model for Campylobacter jejuni - Stamps, Blake W.; Kuroiwa, Janelle; Isidean, Sandra D.; Schilling, Megan A.; Harro, Clayton; Talaat, Kawsar R.; Sack, David A.; Tribble, David R.; Maue, Alexander C.; Rimmer, Joanna E.; Laird, Renee M.; Porter, Chad K.; et al. (Frontiers in Cellular and Infection Microbiology, 2021)
Campylobacter jejuni infection is a leading cause of foodborne disease, common to children, adult travelers, and military populations in low- to middle-income countries. In the absence of a licensed vaccine, efforts to evaluate prophylactic agents are underway. The prophylactic efficacy of a twice-daily, 550 mg dose of the antibiotic rifaximin demonstrated no efficacy against campylobacteriosis in a controlled human infection model (CHIM); however, samples from the CHIM study were utilized to assess how the human gut microbiome responds to C. jejuni infection, and if a ‘protective’ microbiota exists in study participants not developing campylobacteriosis. Statistically significant, but minor, differences in study participant beta diversity were identified during the challenge period (p = 0.002, R2 = 0.042), but no significant differences were otherwise observed. Pre-challenge alpha diversity was elevated in study participants who did not develop campylobacteriosis compared to those who did (p < 0.001), but alpha diversity declined in all study participants from the pre-challenge period to post-discharge. Our work provides insight into gut microbiome shifts observed during a C. jejuni CHIM and following antibiotic treatment. This study utilized a high dose of 1.7 x 105 colony forming units of C. jejuni; future work could include CHIM studies performed with inocula more closely mimicking natural exposure as well as field field studies involving naturally-occurring enteric infections.